2020
DOI: 10.1039/d0en00757a
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of nitrogen stress in rice (Oryza sativa) by ceria nanoparticles

Abstract: This study explored the potential of ceria nanoparticles (CeO2 NPs) to alleviate stress in hydroponic rice caused by low N (LN) and high N (HN) stresses. N contents in plant...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 45 publications
1
42
0
Order By: Relevance
“…[ 27 ] Plants can adjust their phytohormone levels to cope with ambient stress such as that caused by NMs exposure. [ 28 ] Recent studies also showed that CuO and Cu 3 (PO 4 ) 2 can protect soybean plants from sudden death syndrome by modulation of nutritional and phytohormone levels. [28b] CeO 2 NMs also showed alleviation of plant stress caused by nitrogen deficiency or excess by modulation of the antioxidant system and phytohormones.…”
Section: Discussionmentioning
confidence: 99%
“…[ 27 ] Plants can adjust their phytohormone levels to cope with ambient stress such as that caused by NMs exposure. [ 28 ] Recent studies also showed that CuO and Cu 3 (PO 4 ) 2 can protect soybean plants from sudden death syndrome by modulation of nutritional and phytohormone levels. [28b] CeO 2 NMs also showed alleviation of plant stress caused by nitrogen deficiency or excess by modulation of the antioxidant system and phytohormones.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Hao et al reported that the C:N ratio of rice roots increased significantly with the addition of CNTs, which was mainly due to the decrease of N absorption. Another study found that ceria NMs enhanced the activities of key enzyme involved in N assimilation, including GOGAT, GS, and glutamate dehydrogenase (GDH), accounting for the increase of N content in rice . Lahiani et al showed that the photosynthetic electron transfer and CO 2 assimilation in corn leaves were enhanced by 40 mg/L MWCNTs, and the photosynthetic capacity was increased by 10%.…”
Section: Introductionmentioning
confidence: 99%
“…However, at high concentrations, ceria NPs inhibited plant growth in the absence of stress in the hydroponic culture. Therefore, ceria NPs can exert positive effects but their concentration needs to be monitored carefully [ 138 ]. Furthermore, it has been postulated that nanosized ceria may interfere with plant–bacteria interactions at the root level, as demonstrated in a study on nitrogen-fixing symbiotic organisms [ 139 ].…”
Section: (Bio)applicationsmentioning
confidence: 99%